Regulation of Polyunsaturated Fatty Acid Biosynthesis by Seaweed Fucoxanthin and Its Metabolite in Cultured Hepatocytes. Issue 2 (31st October 2013) - Aki, Tsunehiro; Yamamoto, Masaya; Takahashi, Toshiaki; Tomita, Kohki; Toyoura, Rieko; Iwashita, Kazuhiro; Kawamoto, Seiji; Hosokawa, Masashi; Miyashita, Kazuo; Ono, Kazuhisa
Abstract: The effects of a seaweed carotenoid, fucoxanthin, and its physiological metabolite, fucoxanthinol, on the biosynthesis of polyunsaturated fatty acids (PUFA) were investigated using cultured rat hepatoma BRL‐3A. The metabolism of α‐linolenic acid (18:3n‐3) was suppressed by the addition of these carotenoids, resulting in a decrease in the content of eicosapentaenoic acid (20:5n‐3), which suggested a down‐regulation of metabolic enzymes such as fatty acid desaturase and elongase. An increase in the content of docosahexaenoic acid (22:6n‐3), as observed in previous studies in vivo, might be a buffering action to maintain the membrane fluidity. The suppressive effect of fucoxanthinol on ∆6 fatty acid desaturase was not at the level of gene expression but due to specific modifications of the protein via a ubiquitin–proteasome system. A proteomic analysis revealed several factors such as phosphatidylethanolamine‐binding protein that might be involved in the observed action of fucoxanthin. These findings will contribute to studies on the elucidation of the precise molecular mechanisms underlying the regulation of PUFA biosynthesis by fucoxanthin.